When `the show` cannot go on: An investigation into sportsmega-events and responses during the pandemic crisis - Ludvigsen, J. A. L. (International Review for the Sociology of Sport, 2022)
This article examines the relationship between sports mega-events and the coronavirus disease-2019 pandemic. Focusing primarily on the 2020 Summer Olympics and Union of European Football Associations Euro 2020 in football-representing two mega-events that were postponeddue to the pandemic - this article explores the emerging discourses from sport governing bodies,and how these organisations communicated their initial responses to the pandemic between February and May 2020. The article takes a digital qualitative research approach and draws upon frame analysed media sources and public communications. As it proceeds, this article first illuminates how global sports entered a temporary standstill and, second, how sport governing bodies positioned themselves with regard to responding to the global crisis from within the sport-ing sphere. Subsequently, this article emphasises how the relevant responses, as communicated bysport governing bodies, reflected the broader reactive and adaptive pandemic responses apparent within socio-political fields.